Pan-European δ13C values of air and organic matter from forest ecosystems - Hemming, Deborah; Yakir, Dan; Ambus, Per; Aurela, Mika; Besson, Cathy; Black, Kevin; Buchmann, Nina; Burlett, Regis; CESCATTI, ALESSANDRO; Clement, Robert; Gross, Patrick; Granier, André; et al. (Global Change Biology, 2005)
We present carbon stable isotope, δ13C, results from air and organic matter samples collected during 98 individual field campaigns across a network of Carboeuroflux forest sites in 2001 (14 sites) and 2002 (16 sites). Using these data, we tested the hypothesis that δ13C values derived from large-scale atmospheric measurements and models, which are routinely used to partition carbon fluxes between land and ocean, and potentially between respiration and photosynthesis on land, are consistent with directly measured ecosystem-scale δ13C values. In this framework, we also tested the potential of δ13C in canopy air and plant organic matter to record regional-scale ecophysiological patterns. Our network estimates for the mean δ13C of ecosystem respired CO2 and the related ‘discrimination’ of ecosystem respiration, δer and Δer, respectively, were −25.6±1.9‰ and 17.8 ±2.0‰ in 2001 and −26.6±1.5‰ and 19.0±1.6‰ in 2002. The results were in close agreement with δ13C values derived from regional-scale atmospheric measurement programs for 2001, but less so in 2002, which had an unusual precipitation pattern. This suggests that regional-scale atmospheric sampling programs generally capture ecosystem δ13C signals over Europe, but may be limited in capturing some of the interannual variations. In 2001, but less so in 2002, there were discernable longitudinal and seasonal trends in δer. From west to east, across the network, there was a general enrichment in 13C (∼3‰ and ∼1‰ for the 2 years, respectively) consistent with increasing Gorczynski continentality index for warmer and drier conditions. In 2001 only, seasonal 13C enrichment between July and September, followed by depletion in November (from about −26.0‰ to −24.5‰ to −30.0‰), was also observed. In 2001, July and August δer values across the network were significantly related to average daytime vapor pressure deficit (VPD), relative humidity (RH), and, to a lesser degree, air temperature (Ta), but not significantly with monthly average precipitation (Pm). In contrast, in 2002 (a much wetter peak season), δer was significantly related with Ta, but not significantly with VPD and RH. The important role of plant physiological processes on δer in 2001 was emphasized by a relatively rapid turnover (between 1 and 6 days) of assimilated carbon inferred from time-lag analyses of δer vs. meteorological parameters. However, this was not evident in 2002. These analyses also noted corresponding diurnal cycles of δer and meteorological parameters in 2001, indicating a rapid transmission of daytime meteorology, via physiological responses, to the δer signal during this season. Organic matter δ13C results showed progressive 13C enrichment from leaves, through stems and roots to soil organic matter, which may be explained by 13C fractionation during respiration. This enrichment was species dependent and was prominent in angiosperms but not in gymnosperms. δ13C values of organic matter of any of the plant components did not well represent short-term δer values during the seasonal cycle, and could not be used to partition ecosystem respiration into autotrophic and heterotrophic components.
Keywords: carboeuroflux; CO2 fluxes; ecosystem carbon budget; ecosystem respiration; isotopic discrimination; Stable isotopes; δ13C